Parental Gender Stereotypes and Student Wellbeing in China - Shuai Chu; Xiangquan Zeng; Klaus F. Zimmermann (Global Labor Organization (GLO), 2020)
Non-cognitive abilities are supposed to affect student's educational performance, who are challenged by parental expectations and norms. Parental gender stereotypes are shown to strongly decrease student wellbeing in China. Students are strongly more depressed, feeling blue, unhappy, not enjoying life and sad with no male-female differences while parental education does not matter.
Keywords: I12; I26; I31; J16; 330; Gender identity; gender stereotypes; student wellbeing; non-cognitive abilities; mental health; subjective wellbeing